Kebenaran di Era Post-Truth dan Dampaknya bagi Keilmuan Akidah - Chair, Badrul Munir; Adzfar, Zainul (FIKRAH, 2021)
This article discusses the phenomenon of the truth in this post-truth era which does not have a clear theoretical basis and prioritizes emotions and personal beliefs than the objective evidence. But the formation of truth is influentially shaping public opinion. As a result, people indifferently to the scientific truth or factual truth, including in matters of faith. The establish of the truth of faith in the post-truth era is being questioned. This article reveals the aspect of truth that appears in the media as the basis of belief (aqidah). We used the literature study method to determine the formation of truth in the post-truth era in the perspective of the philosophy of science. Specifically, this article will try to answer about how the impact of post-truth on creed scholarship, and how to reaffirm the truth in the post-truth era. The results of this study indicate that emotions and personal beliefs are the target points for alternative truth spreaders in the formation of post-truth. Post-truth can be used as a momentum to test the truth claims made by each religious group. An open truth test is important to do, so that the scientific faith can be an open text. The knowledge of faith will be placed in the context of today's society, so that it can blend with reality.